2013
DOI: 10.1371/journal.pone.0076331
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Bacterial Microbiome of Citrus Plants in Response to ‘Candidatus Liberibacter asiaticus’-Infection and Antibiotic Treatments

Abstract: The bacterial microbiomes of citrus plants were characterized in response to ‘Candidatus Liberibacter asiaticus’ (Las)-infection and treatments with ampicillin (Amp) and gentamicin (Gm) by Phylochip-based metagenomics. The results revealed that 7,407 of over 50,000 known Operational Taxonomic Units (OTUs) in 53 phyla were detected in citrus leaf midribs using the PhyloChip™ G3 array, of which five phyla were dominant, Proteobacteria (38.7%), Firmicutes (29.0%), Actinobacteria (16.1%), Bacteroidetes (6.2%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
1
33
2
1
Order By: Relevance
“…; Zhang et al . ) to test for the presence of Las bacterium. Both healthy and diseased potted plants were exposed to supplemental zinc using a soil drench.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…; Zhang et al . ) to test for the presence of Las bacterium. Both healthy and diseased potted plants were exposed to supplemental zinc using a soil drench.…”
Section: Methodsmentioning
confidence: 99%
“…; Zhang et al . ) and total DNA (100 ng) as the template. For data comparison across real‐time plates, the minimum threshold was set to 100 with drift correction selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of HLB is underscored by the billions of dollars in economic damage and thousands of jobs lost throughout Florida, where L. asiaticus is widespread, that occurred during the first few years of its documented emergence (35). Interestingly, clone library sequencing and PhyloChip surveys have shown citrus-associated microbiota restructure during HLB symptom development, and it has been suggested that the population dynamics of native bacteria can affect the titer of L. asiaticus (17,(36)(37)(38). In the present study, the microbial communities of citrus trees were defined across a number of variables, including HLB symptom severity, geographic location, citrus cultivar, season, and time.…”
mentioning
confidence: 86%
“…11,12 For example, Bove et al reported the effectiveness of penicillin G, 1 (Figure 1), and tetracycline injections for the treatment of infected sweet orange trees. 13 In another paper, Chung and Zhisheng studied the effectiveness of various antibiotic application methods.…”
Section: ■ Introductionmentioning
confidence: 99%